2016
DOI: 10.15252/embr.201642586
|View full text |Cite
|
Sign up to set email alerts
|

TLR 3 downregulates expression of schizophrenia gene Disc1 via MYD 88 to control neuronal morphology

Abstract: Viral infection during fetal or neonatal stages increases the risk of developing neuropsychiatric disorders such as schizophrenia and autism spectrum disorders. Although neurons express several key regulators of innate immunity, the role of neuronal innate immunity in psychiatric disorders is still unclear. Using cultured neurons and in vivo mouse brain studies, we show here that Toll‐like receptor 3 (TLR3) acts through myeloid differentiation primary response gene 88 (MYD88) to negatively control Disrupted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 81 publications
0
63
0
Order By: Relevance
“…Even TLR3, hitherto the exception of the rule reported to be only one using TRIF as an adapter, seems to employ MyD88 to negatively control the expression of psychiatric disorder-related genes such as Disc1 (Disrupted in schizophrenia 1) in neurons. 315 Interestingly, the molecular mechanism coupling TLR3 to downstream signaling elements via MyD88 does not seem to be through the classical TIR:TIR domain interaction, but rather depends on the N-terminal death domain of MyD88 in a novel and yet unresolved mode. 315 TLRs and members of the IL-1R family can activate very similar signaling pathways (reviewed in 298), which are partially conserved in invertebrates and vertebrates.…”
Section: Signal Initiation In the Il-1r Family And The Myddosomementioning
confidence: 99%
See 1 more Smart Citation
“…Even TLR3, hitherto the exception of the rule reported to be only one using TRIF as an adapter, seems to employ MyD88 to negatively control the expression of psychiatric disorder-related genes such as Disc1 (Disrupted in schizophrenia 1) in neurons. 315 Interestingly, the molecular mechanism coupling TLR3 to downstream signaling elements via MyD88 does not seem to be through the classical TIR:TIR domain interaction, but rather depends on the N-terminal death domain of MyD88 in a novel and yet unresolved mode. 315 TLRs and members of the IL-1R family can activate very similar signaling pathways (reviewed in 298), which are partially conserved in invertebrates and vertebrates.…”
Section: Signal Initiation In the Il-1r Family And The Myddosomementioning
confidence: 99%
“…315 Interestingly, the molecular mechanism coupling TLR3 to downstream signaling elements via MyD88 does not seem to be through the classical TIR:TIR domain interaction, but rather depends on the N-terminal death domain of MyD88 in a novel and yet unresolved mode. 315 TLRs and members of the IL-1R family can activate very similar signaling pathways (reviewed in 298), which are partially conserved in invertebrates and vertebrates. 316 As discussed above, this is due to the fact that the activated TIR-containing receptors create intracellularly the TIR:TIR scaffold required for recruiting MyD88 (or, in the case of TLR, TRIF), which is the prerequisite for downstream signaling.…”
Section: Signal Initiation In the Il-1r Family And The Myddosomementioning
confidence: 99%
“…oligodendrocytes (Okun et al, 2011) with its activation shown to negatively regulate axonal growth, reduce neural precursor cell proliferation and contribute to the long term CNS effects associated with maternal viral infection including Zika virus-induced microcephaly (Cameron et al, 2007;Lathia et al, 2008;Reisinger et al, 2015;Faizan et al, 2016;Chen et al, 2017). In addition, TLR3 was also revealed to regulate spinal cord synaptic transmission and central sensitisation, thus highlighting its critical role in pruritus (Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal immune activation increases the likelihood of offspring developing schizophrenia and ASD via both innate and adaptive immune responses (Choi et al, 2016;Filiano et al, 2016;Kugelberg, 2016;Wu et al, 2017). In addition to peripheral immune responses, neurons can also use their own Toll-like receptors to detect environmental insults and control growth of their axons, dendrites and synapses (Liu et al, 2013;Chen et al, 2017;Hung et al, 2018). Thus, both the peripheral immune system and neuronal responses are involved in the impacts of infection on neurodevelopmental disorders at early developmental stages (Figure 1).…”
Section: Environmental Factors and Epigenetic Controlmentioning
confidence: 99%